The design of an FPGA based embedded data collection system, with application to surface profiling - Tidball, Kyle D. (Kansas State University, 2012)
Over the last several years, the use of Field Programmable Gate Arrays, or FPGAs, has become increasingly popular in the embedded systems field. However, FPGAs are typically used only as a coprocessor or dedicated DSP. This project proposes that an embedded system can realize a performance gain over a traditional microprocessor-based design and be made more flexible and extensible by using an FPGA as the primary processing device in the embedded system. Basing a design on an FPGA also allows new features to be much more rapidly developed and integrated into the system. This will be shown by designing an FPGA based embedded system for Surface Systems & Instruments’ Walking Profiler device. The system will include support for rotary encoders, an incline sensor for data collection, and an Ethernet protocol for communication with a Windows computer. The implementation of a sub sampling distance measuring algorithm will be used to demonstrate the tradeoffs between hardware, software, and development times.
Keywords: FPGA; Digital hardware design; Road profiling; Electrical Engineering (0544)